2022
DOI: 10.1136/bmjopen-2021-060555
|View full text |Cite
|
Sign up to set email alerts
|

Why do people consent to receiving SARS-CoV-2 vaccinations? A representative survey in Germany

Abstract: ObjectiveTo answer the question: Why do people consent to being vaccinated with novel vaccines against SARS-CoV-2?DesignRepresentative survey.SettingOnline panel.Participants1032 respondents of the general German population.MethodA representative survey among German citizens in November/December 2021 that resulted in 1032 complete responses on vaccination status, sociodemographic parameters and opinions about the COVID-19 situation.ResultsAlmost 83% of the respondents were vaccinated. The major motivation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This is because non-financial motivations such as reputation are particularly important in motivating contributions to public goods 91 93 , and these can be ‘crowded out’ by financial incentives 27 – 29 . This is admittedly complicated by the fact that the same behavior may simultaneously involve private benefits while also being a contribution to the public good, as is the case for vaccination 59 ; when this is the case, one should try to anticipate people’s motivations, e.g., whether most people are primarily motivated to protect themselves from COVID-19, or whether they are not so worried about COVID-19 for themselves, and might instead be motivated by the protective effects of vaccination on others, and the potential to achieve herd immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because non-financial motivations such as reputation are particularly important in motivating contributions to public goods 91 93 , and these can be ‘crowded out’ by financial incentives 27 – 29 . This is admittedly complicated by the fact that the same behavior may simultaneously involve private benefits while also being a contribution to the public good, as is the case for vaccination 59 ; when this is the case, one should try to anticipate people’s motivations, e.g., whether most people are primarily motivated to protect themselves from COVID-19, or whether they are not so worried about COVID-19 for themselves, and might instead be motivated by the protective effects of vaccination on others, and the potential to achieve herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, non-financial motivations in general, and reputational motivations in particular play an outsized role in motivating COVID-19 vaccination 57 and evasion thereof 58 . For instance, in survey data from Germany, 65.8% of respondents cited “I want to contribute to eradicating the virus” as one of their top three motivations for vaccination, and 21.2% cited “My social environment exerts pressure” 59 . Third, proposed financial incentives for vaccination tend to be relatively small—typically the equivalent of about 25 USD.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 However, the lack of sufficient verification of the safety and side effects of the COVID-19 vaccines suggests that these should be given only to those who wish to receive them, and RCTs of the COVID-19 vaccines may violate medical ethics. 31 In addition, with regard to lockdown policies, it is probably not possible to make simple comparisons because the political, social, and economic conditions in each country play important roles. 32,33 It has been reported that lockdown policies had a significant impact on socioeconomic activity and the maintenance of physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth qualitative survey involving 33 German participants identified four primary themes that influenced the decision to receive a COVID-19 vaccine: (i) assessment of the benefits and risks of being vaccinated against COVID-19; (ii) influence of existing social and political conditions; (iii) emotional responses to the pandemic and its social and political impact; and (iv) trust and confidence in health authorities and the vaccines themselves [20]. Recurrent themes across multiple studies in both Germany and Europe as a whole included reasons such as low levels of trust in healthcare authorities and COVID-19 vaccines, concerns about potential side effects, and alignment with right-wing political stances [21][22][23][24][25][26]. Thus, it appears that there are fundamental concerns about vaccination that are also intertwined with political ideologies.…”
Section: Discussionmentioning
confidence: 99%